Diagnosis, Management and Prevention of Hepatitis C in Pakistan 2017 - Umar, Muhammad; Khaar, Hamama-tul-Bushra; Akhter, Tayyab Saeed; Aslam, Faiza; Ahmad, Syed Irfan; Asghar, Rai Mohammad; Khurram, Mohammad; Hussain, Tassawar; Salamat, Amjad; Khan, Anwar A.; Hadi, Fazal e; Minhas, Zahid Mahmood; et al. (Journal of Ayub Medical College Abbottabad, 2017)
Aims and Objectives: Since the advent of direct acting antiviral agents, there is a revolutionary change in the management of HCV infection. Newer drugs with different mechanism of action are being introduced and are expected to be available in coming few months in Pakistan as well. The main purpose of the guideline is to review and induct the latest research in field of HCV infection in Pakistani perspective so that our healthcare professionals can apply the new recommendations in timely and judicial manner. Target groups of guidelines are general physicians treating hepatitis C, hepatologists and gastroenterologists. Other beneficiaries of these guidelines are public health institutions of Pakistan, which provide free treatment to deserving patients under National Hepatitis Prevention and Control Program and Pakistan Bait-ul- Mal Program. Methodology: These guidelines are based on the review of National consensus practice guidelines: Diagnosis, Management and Prevention of Hepatitis C Pakistan 2009. Published data in National and International Journals searched with the help of Google search and pub med, and 2015-16 guidelines of HCV by AASLD, EASL, APASL and WHO. Local studies are preferably added with references to enhance the Pakistani perspective. Evidence was also taken from published studies. Recommendations have been based upon evidence from national publications on the subject and scientific presentations at national liver meeting as well from experts' personal experience and opinion